Methods of Organizational Conflict Management and the Leadership Styles Used by the Heads of Academic Departments at the University of Duhok - Bshkush Jahfar Abdullah (Zanco Journal of Humanity Sciences)
The present study aimed to investigate the association between methods of organizational conflict management and the leadership styles used by the heads of academic departments at the University of Duhok. The study controls for gender, the academic title, years of service and the name of the college. The research population consisted of all the teaching staff at the University of Duhok, whose number is (1607). The researcher used multi-stage random sample of (240) male and female heads of departments. The researcher prepared two research instruments. The first one to measure organizational conflict management methods, which consisted of (20) items and divided into four themes: confrontation, avoidance, appeasement, and concession. The second instrument to measure the leadership styles, which consisted of (30) items distributed divided three themes: democratic, autocratic, and chaotic